4-Methoxy-N′-(2-methoxybenzylidene)benzohydrazide - Zhang, Xinyou (International Union of Crystallography, 2009)
In the title compound, C(16)H(16)N(2)O(3), the two benzene rings are inclined to one another by 75.4 (2)°, and the molecule adopts an E configuration about the C=N bond. In the crystal structure, symmetry-related molecules are linked via intermolecular N—H⋯O hydrogen bonds, forming chains running parallel to the c axis.